2008
DOI: 10.1558/sols.v2i1.131
|View full text |Cite
|
Sign up to set email alerts
|

The role of Gallo in the identity of Upper-Breton school pupils of the language variety and their parents

Abstract: Whilst recent studies have provided pivotal insights into the relationship between Bretons and the principle languages of Brittany, Breton and French, this paper aims to shed light on the relationship between Brittany’s northern French near language (Oïl) variety, Gallo, and the identity of the inhabitants of the territory with which it is historically associated, Upper-Brittany. This is done through questionnaires of both a quantitative and qualitative nature and follow-up interviews with school pupils of Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Basse-Bretagne corresponds to the Breton area (Brezhoneg in the Celtic language) and Haute-Bretagne is the region where Gallo varieties are still used. According to previous studies, Nolan (2008b), and Blanchet and Le Coq (2007), Gallo speakers did not express positive representations of the language and culture of Haute-Brittany.…”
Section: Introductionmentioning
confidence: 72%
“…Basse-Bretagne corresponds to the Breton area (Brezhoneg in the Celtic language) and Haute-Bretagne is the region where Gallo varieties are still used. According to previous studies, Nolan (2008b), and Blanchet and Le Coq (2007), Gallo speakers did not express positive representations of the language and culture of Haute-Brittany.…”
Section: Introductionmentioning
confidence: 72%
“…This perceived dialectal status is frequently used to deny requests for the opening of new Gallo classes despite activist claims that there exists public demand for this (cf. Nolan 2006Nolan , 2008a. Resources for the provision of such classes have also been placed under severe pressure since the 2002 withdrawal of the Gallo option for trainee teachers at the Institut universitaire de formation des maîtres ('teacher training college', IUFM).…”
Section: Rl Activism In the Context Of Language Emancipation With Parmentioning
confidence: 99%
“…However, it has equally shown that Gallo's status continues to be a source of debate within the education system and in Breton society in general (cf. Nolan 2006Nolan , 2008aNolan , 2008b …”
Section: Rl Activism In the Context Of Language Emancipation With Parmentioning
confidence: 99%
See 1 more Smart Citation